Common bean seed quality as affected by cover crop mixtures and nitrogen fertilization - Pedrinho, Alexandre [UNESP]; Mariano, Eduardo [UNESP]; Merloti, Luis Fernando [UNESP]; de Sá, Marco Eustáquio [UNESP] (Southern Cross Publishing, 2019)
Several studies have shown that cover crop can increase common bean (Phaseolus vulgaris L.) yield. However, little is known about the influence of cover crop mixtures in association with topdressing N fertilization on common bean seed quality. We, therefore, evaluated the physiological quality of common bean seeds produced under cover crop residues and N fertilized in a no-till farming system. A 5 × 4 factorial experiment (cover crops and N rates) was performed under field conditions in Mato Grosso do Sul, Brazil. Single-specie and cover crops mixtures [pearl millet (Pennisetum glaucum), pearl millet-jack bean (P. glaucum; Canavalia ensiformis), pearl millet-pigeon pea (P. glaucum; Cajanus cajan), pearl millet-sunn hemp (P. glaucum; Crotalaria juncea), and pearll millet-velvet bean (P. glaucum; Mucuna pruriens)] were grown and common bean was planted in succession. Nitrogen fertilizer (50, 100, and 150 kg N ha -1 ) was topdressed applied to common bean at the V4 stage. At maturity, common bean plants were harvested, and physiological quality of seeds was assessed. The first germination count, final germination, germination speed index, accelerated aging, and N and protein concentration were influenced by cover crop residues and/or N rates (main effect). A cover crop × N rate interaction was observed for seedling dry biomass after germination and accelerated aging. All treatments produced seeds with high physiological quality. Although the cover crops showed variable results, the application of 100 kg N ha -1 in topdressing slightly improved seed quality attributes compared to the other N rate treatments. We conclude that addition of N fertilizer and cover crop treatments does not affect common bean seed quality to a large extent.
Keywords: Legume; Nitrogen fertilizer; Pearl millet; Phaseolus vulgaris L.; Physiological quality